Resilience and Adaptation of Micro-Enterprises within a Declining Tourism Ecosystem: A Qualitative Case Study of Cemara Beach, West Lombok, Indonesia - Ivaska Dean Arthur Sarosa; Diswandi, Diswandi (Future Tecno-Science Publisher, 2025)
This study aims to examine the dynamics of micro-enterprises within the tourism ecosystem during periods of tourist decline and to identify the main causes of such downturns at Cemara Beach, Lembar Selatan Village, West Lombok Regency. A qualitative approach was employed, using data collection techniques including in-depth interviews, participatory observation, and documentation. Content analysis was utilized to identify key themes and patterns from the collected data. The findings reveal that the decline in tourism was primarily driven by poor infrastructure, inadequate promotional efforts, limited supporting facilities, and weak synergy between the government and local communities. This decline has directly impacted micro, small, and medium enterprises (MSMEs), leading to reduced revenue, downsizing of operations, and business closures. Nevertheless, several MSME actors demonstrated resilience by diversifying their products, utilizing social media for marketing, and initiating informal collaborations with fellow entrepreneurs.